Strickberger's Evolution The Integration of Genes, Organisms and Populations - Hall, Brian Keith Hallgrimsson, Benedikt (Jones and Bartlett, 2008)
This book presents evolution of organisms, how genes cell and embryonic development provide the organic framework by which evolution occurs and how evolution and society have an impact on one another. This is very useful book.